The immunologic effects of mesalamine in treated HIV-infected individuals with incomplete CD4+ T cell recovery: a randomized crossover trial. - Ma Somsouk; Richard M Dunham; Michelle Cohen; Rebecca Albright; Mohamed Abdel-Mohsen; Teri Liegler; Jeffrey Lifson; Michael Piatak; Robert Gorelick; Yong Huang; Yuaner Wu; Priscilla Y Hsue; et al. (PLoS ONE)
Unlabelled The anti-inflammatory agent, mesalamine (5-aminosalicylic acid) has been shown to decrease mucosal inflammation in ulcerative colitis. The effect of mesalamine in HIV-infected individuals, who exhibit abnormal mucosal immune activation and microbial translocation (MT), has not been established in a placebo-controlled trial. We randomized 33 HIV-infected subjects with CD4 counts <350 cells/mm3 and plasma HIV RNA levels <40 copies/ml on antiretroviral therapy (ART) to add mesalamine vs. placebo to their existing regimen for 12 weeks followed by a 12 week crossover to the other arm. Compared to placebo-treated subjects, mesalamine-treated subjects did not experience any significant change in the percent CD38+HLA-DR+ peripheral blood CD4+ and CD8+ T cells at week 12 (P = 0.38 and P = 0.63, respectively), or in the CD4+ T cell count at week 12 (P = 0.83). The percent CD38+HLA-DR+ CD4+ and CD8+ T cells also did not change significantly in rectal tissue (P = 0.86, P = 0.84, respectively). During the period of mesalamine administration, plasma sCD14, IL-6, D-dimer, and kynurenine to tryptophan ratio were not changed significantly at week 12 and were similarly unchanged at week 24. This study suggests that, at least under the conditions studied, the persistent immune activation associated with HIV infection is not impacted by the anti-inflammatory effects of mesalamine. Trial registration ClinicalTrials.gov NCT01090102.